2017
DOI: 10.3892/ol.2017.7422
|View full text |Cite
|
Sign up to set email alerts
|

G‑CSF producing oral carcinoma with diffuse uptake of FDG in the bone marrow: A case report

Abstract: Abstract.A 78-year-old male patient was referred to the Department of Oral Surgery, Hokuto Hospital (Obihiro, Japan) for painless swelling on the left neck and tongue. Histopathological examination of a biopsy specimen resulted in a diagnosis of squamous cell carcinoma of the tongue. Imaging examinations revealed cervical lymph node metastases on both sides, along with diffuse uptake of 18 F-fluorodeoxyglucose (FDG) in the bone marrow of the spine and pelvis. Hematologic tests revealed an increased white blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
3
8
1
Order By: Relevance
“…In most studies, G CSF was immunohistochemically confined to tumour cells. However, one study reported a negative result for G-CSF immunohistochemical staining (9) and in our study, as well as some of the tumour cells, some of the infiltrating leukocytes stained positiveIy for G-CSF. There has been speculation that the rapid secretion of G-CSF from tumour cells may lead to negative staining results (9).…”
Section: Discussioncontrasting
confidence: 44%
“…In most studies, G CSF was immunohistochemically confined to tumour cells. However, one study reported a negative result for G-CSF immunohistochemical staining (9) and in our study, as well as some of the tumour cells, some of the infiltrating leukocytes stained positiveIy for G-CSF. There has been speculation that the rapid secretion of G-CSF from tumour cells may lead to negative staining results (9).…”
Section: Discussioncontrasting
confidence: 44%
“…In a retrospective study of 28 children suspected of leukemia progression or recurrence during / after chemotherapy or allo-HSCT, 14 cases with positive 18 F-FDG-PET/CT scans were associated with increased blasts in bone marrow biopsies, and the mean SUV max was significantly higher than what is seen with infectious diseases ( 15 ). In addition, G-CSF induced high uptake of FDG in bone marrow system was always diffusely distributed ( 16 , 17 ). In the second case, the adjacent bilateral bone biopsy (day +133) and PET/CT scan (day +143) demonstrated that the focal bone marrow hypermetabolism of 18 F-FDG was caused by the asymmetric distribution of the blasts.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] The overall mortality rate of these tumors is 65.5%, and the overall 1-, 2-, and 5-year survival rate is 57.9%, 44.8%, and 17.7%, respectively. [ 8 9 ] This patient was initially diagnosed with maxillary sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…reported the first case of a G-CSF-producing tumor and proposed the following criteria for diagnosing G-CSF-producing tumors: (1) leukocytosis with neutrophil predominance; (2) elevated serum and urine G-CSF levels; (3) normalization of WBC count and serum G-CSF level after removal of the tumor; and (4) increased G-CSF in tumor tissues. [ 8 9 ] The gold standard to diagnose of G-CSF-producing tumor in this case was the laboratory finding. It showed elevated WBC and G-CSF levels, which were accompanied by normalization after the CRT and increase at the recurrence.…”
Section: Discussionmentioning
confidence: 99%